Investigating the role of divertor geometry on density build-up in the island divertor - N. Maaziz; F. Reimold; V.R. Winters; D. Bold; Y. Feng; V. Perseo (Nuclear Materials and Energy)
The island divertor has been proposed for power and particle exhaust in stellarators. It is investigated in the Wendelstein 7-X (W7-X) experiment. The divertor capabilities such as particle exhaust or radiative power dissipation scale with the divertor density. However, significantly lower divertor density has been obtained in W7-X in comparison to tokamaks and no high-recycling scaling is observed. To alleviate the impact of the complicated geometry, a simplified geometry model for the island divertor in EMC3-EIRENE is developed and used to investigate the effect of the divertor target geometry. We show that compared to the open divertor, a closed divertor geometry leads to higher achievable densities and in particular a much stronger scaling of the target density with respect to the separatrix density.